2015
DOI: 10.17795/dcej-5634
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Tissue Eosinophilia in Squamous Cell Carcinoma of Head and Neck

Abstract: Background: Tumor-associated tissue eosinophilia (TATE) is reported in different cancers of human body but its exact role is not yet defined in head and neck squamous cell carcinoma (HNSCC). Objectives: The current study aimed to assess the relationship between TATE and histopathologic grading, age and gender of patients with HNSCC. Materials and Methods:In this cross-sectional study, 90 paraffin-embedded blocks of HNSCC samples were sectioned and stained with Sirius red (a histochemical staining). Then the eo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…2 A retrospective review by Hirshberg et al 7 suggested that the lesion is self-healing with the duration ranging from several weeks to one year. Observations by Rahrotaban et al 8 revealed the anti-tumour role of eosinophils with a positive correlation between the degree of tumour differentiation and tumourassociated tissue eosinophilia (poorly differentiated tumours had lesser tissue eosinophilia). Bankur et al 9 performed a quantitative study on tumour-associated tissue eosinophils with various histological grades of oral squamous cell carcinoma and suggested that tissue eosinophilia is higher in well-differentiated squamous cell carcinoma compared to other grades.…”
Section: Case Reportmentioning
confidence: 97%
“…2 A retrospective review by Hirshberg et al 7 suggested that the lesion is self-healing with the duration ranging from several weeks to one year. Observations by Rahrotaban et al 8 revealed the anti-tumour role of eosinophils with a positive correlation between the degree of tumour differentiation and tumourassociated tissue eosinophilia (poorly differentiated tumours had lesser tissue eosinophilia). Bankur et al 9 performed a quantitative study on tumour-associated tissue eosinophils with various histological grades of oral squamous cell carcinoma and suggested that tissue eosinophilia is higher in well-differentiated squamous cell carcinoma compared to other grades.…”
Section: Case Reportmentioning
confidence: 97%
“…Some researchers consider eosinophils as the cause of tumor progression and poor disease prognosis, and some believe that they contribute to a favorable prognosis and a high survival in patients. [8,9] Many studies have examined their density in oral squamous cell carcinoma, [10] but few have assessed their density and arrangement in salivary gland tumors, and none have compared their density in common benign and malignant salivary gland tumors. The present study was therefore conducted to examine this issue and investigate the relationship between eosinophil density and the degree of malignancy in malignant salivary gland tumors.…”
Section: Introductionmentioning
confidence: 99%